Fire and smoke alert for enhanced safety and family environment fumisafe - Norazmi, Nur Adam; Zainuddin, Aznilinda; Onn, Munirah; Kasri, Nur Faizal (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The FUMISAFE (Fire and Smoke Alert for Enhanced Safety and Family Environment) project introduces an innovative solution to improve fire safety in residential spaces. Traditional fire alarm systems primarily rely on detecting smoke, which often delays response times in scenarios where flames appear first. FUMISAFE leverages advanced infrared flame sensors, smoke detectors, and IoT technology to provide quicker and more accurate identification of fire hazards. With IoT integration, the system offers real-time updates directly to the user's mobile phone, ensuring immediate awareness and response. Furthermore, the system is solar powered, making it environmentally friendly and independent of grid electricity, ensuring continuous functionality even during power outages. FUMISAFE combines essential components, including an LCD display for on-site notifications, a buzzer and LED indicators for local alerts, and a microcontroller that processes data for comprehensive monitoring. Its affordability, reliability, and eco-friendly design make it a practical choice for modern households. Beyond safeguarding lives and properties, FUMISAFE is aligned with the United Nations Sustainable Development Goal (SDG) 11: Sustainable Cities and Communities by enhancing safety and promoting the adoption of sustainable technology. Its strong commercialization potential makes it a scalable and adaptable solution for smart home applications.